Mechanical damage thresholds for hematomas near gas-containing bodies in pulsed HIFU fields. (7th November 2022) - Ponomarchuk, Ekaterina M; Hunter, Christopher; Song, Minho; Khokhlova, Vera A; Sapozhnikov, Oleg A; Yuldashev, Petr V; Khokhlova, Tatiana D
Abstract: Objective . Boiling histotripsy (BH) is a novel high intensity focused ultrasound (HIFU) application currently being developed for non-invasive mechanical fractionation of soft tissues and large hematomas. In the context of development of BH treatment planning approaches for ablating targets adjacent to gas-containing organs, this study aimed at investigation of the ultrasound pressure thresholds of atomization-induced damage to the tissue-air interface and correlation of the danger zone dimensions with spatial structure of nonlinear HIFU field parameters. Approach . A flat interface with air of freshly clotted bovine blood was used as an ex vivo model due to its homogenous structure and higher susceptibility to ultrasound-induced mechanical damage compared to soft tissues. Three 1.5 MHz transducers of different F -numbers (0.77, 1 and 1.5) were focused at various distances before or beyond a flat clot surface, and a BH exposure was delivered either at constant, high-amplitude output level, or at gradually increasing level until a visible damage to the clot surface occurred. The HIFU pressure field parameters at the clot surface were determined through a combination of hydrophone measurements in water, forward wave propagation simulation using 'HIFU beam' software and an image source method to account for the wave reflection from the clot surface and formation of a standing wave. The iso-levels of peak negative pressure in the resulting HIFU field were correlated to the outlines of surface erosion to identify the danger zone around the BH focus. Main results . The outline of the danger zone was shown to differ from that of a typical BH lesion produced in a volume of clot material. In the prefocal area, the zone was confined within the 4 MPa contour of the incident peak-to-peak pressure; within the main focal lobe it was determined by the maximum BH lesion width, and in the postfocal area—by the transverse size of the focal lobe and position of the first postfocal pressure axial null. Significance . The incident HIFU pressure-based danger zone boundaries were outlined around the BH focus and can be superimposed onto in-treatment ultrasound image to avoid damage to adjacent gas-containing bodies.